P265 Open approach for ileocolic resection in Crohn's disease in the era of minimally invasive surgery: indications and perioperative outcomes in a referral centre. (21st January 2022) - Calini, G; Abdalla, S; Abd El Aziz, M A; Benammi, S; Merchea, A; Behm, K T; Mathis, K L; Larson, D W
Abstract: Background: Minimally invasive surgery (MIS) is the first-line approach for ileocolic resection in patients with Crohn's disease (CD) and it is safe and feasible even in complex cases. However, an open approach is still required, but indications to open ileocolic resection for CD are not well described. Methods: All consecutive adult patients with CD who underwent elective ileocolic resection in the Departments of Colon and Rectal Surgery at Mayo Clinic Rochester, Minnesota and Jacksonville, Florida between September 2014 and March 2021 were included and divided into "open" and "MIS" groups. Open approach was defined as upfront laparotomy, MIS included laparoscopic and robotic approaches, and conversion was defined as incision made earlier than planned. Indications to open approach were retrospectively reviewed by two authors, and any incongruity was resolved. Analogous indications were also assessed in the MIS group, as appropriate. Indications, baseline, perioperative characteristics, and short-term postoperative outcomes were compared between open and MIS. Results: Among 319 ileocolic resections for CD, 45 (14.1%) were open and 274 (85.9%) MIS. Indications for open approach were severe disease, adhesions at previous surgery, history of abdominal sepsis, multifocal and extensive disease, abdominal wall involvement, concomitant open procedures, small bowel dilatation, and anaesthesiologic contraindications (Table 1). In addition, two or more of the above indications were present in 40 patients (89%) in the open group, while only in 6 patients (2%) in the MIS group (p<0.001). Compared to MIS patients, patients undergoing open ileocolic resection were older, with longer CD duration, more previous surgery and preoperative intra-abdominal abscess drainage (Table 2). Nine patients were converted in the MIS group (3.3%). Intraoperatively, open group had more adhesiolysis ≥45 min, more intraoperative complications, more blood loss, more primary stoma, less anastomosis, and longer operative time (Table 3). Postoperatively, they had more overall postoperative complications, ileus, surgical site infections, dehydration, vascular thromboembolism, higher severity by Clavien-Dindo classification, and longer length of stay (Table 4). Conclusion: Overall rate of open approach ileocolic resection for CD was 14 % during a 7-years period in a referral centre. Open approach was the only operation performed in cases of abdominal wall involvement, concomitant open procedures, and anaesthesiologic contraindication. In addition, the presence of at least two indications, predicting high technical complexity, may be considered as a no-go for the MIS approach in ileocolic resections for CD.